Characterization of virus-mediated immunogenic cancer cell death and the consequences for oncolytic virus-based immunotherapy of cancer - Ma, Jing (Cell Death Dis, 2020)
Oncolytic viruses have the potential to induce immunogenic cell death (ICD) that may provoke potent and long-lasting anti-cancer immunity. Here we aimed to characterize the ICD-inducing ability of wild-type Adenovirus (Ad), Semliki Forest virus (SFV) and Vaccinia virus (VV). We did so by investigating the cell death and immune-activating properties of virus-killed tumor cells. Ad-infection of tumor cells primarily activates autophagy, but also activate events of necroptotic and pyroptotic cell death. SFV infection on the other hand primarily activates immunogenic apoptosis while VV activates necroptosis. All viruses mediated lysis of tumor cells leading to the release of danger-associated molecular patterns, triggering of phagocytosis and maturation of dendritic cells (DCs). However, only SFV-infected tumor cells triggered significant T helper type 1 (Th1)-cytokine release by DCs and induced antigen-specific T-cell activation. Our results elucidate cell death processes activated upon Ad, SFV, and VV infection and their potential to induce T cell-mediated anti-tumor immune responses. This knowledge provides important insight for the choice and design of therapeutically successful virus-based immunotherapies.